1991
DOI: 10.1029/90gb02279
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon decay and oxygen utilization in the Deep Atlantic Ocean

Abstract: A parameter based on the sum of the concentrations of PO4 and O2 (divided by the Redfield coefficient‐ΔO2/δPO4) is used to separate the contributions of the northern and southern components to deep waters in the Atlantic. This separation allows the amount of radiocarbon lost by radiodecay and the amount of oxygen lost to respiration during residence in the deep Atlantic to be calculated. Maps of these quantities reveal strong west to east gradients and weak north to south gradients consistent with ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 19 publications
9
77
1
Order By: Relevance
“…Below 1500 m, both N+N and phosphate show an average decrease over the 11-year period rather than the increase that would be expected from remineralization of organic matter. There is no observational evidence for changes in sign between the ratios of nutrients and carbon Away from the bottom and surface where silica (opal) dissolution, formation, and uptake by organisms can be significant, silicate is nearly conservative [Broecker et al, 1985[Broecker et al, , 1991 It is difficult to justify a large organic flux to account for the O2 consumption that does not produce a corresponding enrichment of phosphate and N+N. Maximum nutrient enrichment takes place at or near the depth of the O2 minimum layer where maximum phosphate and nitrate concentrations are found due to mineralization of organic matter reaching this depth.…”
Section: Zonally Averaged Difference Profilesmentioning
confidence: 99%
“…Below 1500 m, both N+N and phosphate show an average decrease over the 11-year period rather than the increase that would be expected from remineralization of organic matter. There is no observational evidence for changes in sign between the ratios of nutrients and carbon Away from the bottom and surface where silica (opal) dissolution, formation, and uptake by organisms can be significant, silicate is nearly conservative [Broecker et al, 1985[Broecker et al, , 1991 It is difficult to justify a large organic flux to account for the O2 consumption that does not produce a corresponding enrichment of phosphate and N+N. Maximum nutrient enrichment takes place at or near the depth of the O2 minimum layer where maximum phosphate and nitrate concentrations are found due to mineralization of organic matter reaching this depth.…”
Section: Zonally Averaged Difference Profilesmentioning
confidence: 99%
“…when it is assigned zero age, is of particular interest. For example, the estimation of rates of ocean respiration or CaCO 3 dissolution from cumulative tracer changes Broecker et al, 1991;Feely et al, 2002) requires reliable age determinations. 14 C-ages of several hundred years for waters actually in contact with the atmosphere can thus pose a severe problem.…”
Section: W Koeve Et Almentioning
confidence: 99%
“…The inter-hemispheric exchange in the atmosphere is slow as reflected by the strong hemispheric gradients in gas phase concentrations of POPs (10) and the north-south atmospheric delivery is less efficient than west-east within the Southern Hemisphere (3) . It would take several hundred years for seawater formed in the Arctic to travel to the Southern Ocean according to the 14 C data (11,12) and modeling studies found the transport time for…”
Section: Introductionmentioning
confidence: 99%